Topical 5-aminolevulinic acid photodynamic therapy for genital vitiligo - Tingting Gao; Zhao Feng; Jing Ye; Meihua Chen; Xiaochun Guan; Yuan Wan; Li Qin (Photodiagnosis and Photodynamic Therapy)
Vitiligo is an acquired chronic depigmentary skin disorder which results from the destruction of melanocytes. The clinical characteristic of vitiligo is the development of white macules due to the loss of functioning melanocytes in the skin or hair. Vitiligo in the genital area brings about a serious psychological impact on individuals. However, the choices of treatment for genital vitiligo are scarce. This study sheds light on the leverage of 5-ALA (5-Aminolevulinic Acid) Photodynamic Therapy (PDT) for the management of genital vitiligo. Nine patients with genital vitiligo who underwent 20 % ALA-PDT treatment were reported. The results revealed that the treatment protocol simulated melanocyte regeneration in the patients effectively. ALA-PDT exerts significant anti-inflammatory effects by reducing pro-inflammatory cytokines and inducing regulatory T cells, which may help suppress the autoimmune response involved in vitiligo pathogenesis. Notably, five patients who were defined as responders showed moderate to excellent improvement in repigmentation and the treatment was well tolerated in all cases. Our findings suggest that ALA-PDT is a potential treatment option for genital vitiligo.